Gold-catalyzed enantioselective synthesis of axially chiral compounds - Dong, Yirong; Wang, Tao (Advanced synthesis & catalysis, 2025)
This review provides an overview of the advances in gold-catalyzed synthesis of axially chiral compounds. The published results to date on this topic are categorized by the type of chiral axis, highlighting the structure of ligands, the reaction scope, and mechanistic insights. The challenges and the future directions of this field are also discussed.